Therapeutics for fulminant hepatitis caused by enteroviruses in neonates - Wang, Li-Chiu; Tsai, Huey-Pin; Chen, Shun-Hua; Wang, Shih-Min (Frontiers in Pharmacology, 2022)
Neonatal infection with nonpolio enteroviruses (EV) causes nonspecific febrile ill-nesses and even life-threatening multiorgan failure. Hepatitis that often results in hepatic necrosis followed by disseminated intravascular coagulopathy is one of the most severe and frequent fatal neonatal EV infection complications. Coxsackievirus B (CVB) 1–5 and many echoviruses have been most commonly identified. Neonatal EV infection treatment has usually involved initial supportive care. Studies for CVB and echovirus infection treatments were developed for a one-third century. Intravenous immunoglobulin and pleconaril therapy were performed in some clinical trials. Additionally, other studies demonstrated antiviral and/or anti-inflammatory pathogenesis mechanisms of neonatal EV hepatitis in in vitro or in vivo models. These treatments represented promising options for the clinical practice of neonatal EV hepatitis. However, further investigation is needed to elucidate the whole therapeutic potential and safety problems.